Agroecology in livestock systems in low- and middle- income countries: Managing synergies and trade-offs - Masso, C.; Alary, V.; Burkart, S.; Caron, A.; Ezekannagha, O.; Flintan, Fiona E.; Frija, A.; Geck, M.S.; Habermann, Birgit; Kumar, G.; Kumar, S.; Malaiappan, S.; et al. (2025)
Agroecology offers a practical and evidence-based pathway to making livestock systems more sustainable, climate-resilient, and equitable. By integrating ecological principles with traditional knowledge, diversified production, and social inclusion, agroecological livestock systems can reduce environmental impacts, improve animal health and productivity, support safer and more diverse diets, and strengthen livelihoods through circular nutrient flows and resource efficiency.